Experimental investigation of three distinct mechanisms for the transition from sheet to cloud cavitation. (15th November 2022) - Zhang, Guangjian; Zhang, Desheng; Ge, Mingming; Petkovšek, Martin; Coutier-Delgosha, Olivier
Highlights: We point out the inappropriate classification of combining condensation shock and collapse-induced pressure wave mechanisms in the literature. X-ray phase contrast imaging enhances significantly the vapour-liquid interfaces enabling a more detailed visualization of the two-phase structures. Three different types of mechanisms responsible for large cloud shedding are revealed using experimental measurements. Abstract: The conventional high-speed images of cavitation with a set of X-ray phase contrast images reveal the presence of three different types of mechanisms responsible for large cloud shedding: re-entrant jet mechanism, condensation shock wave mechanism, and collapse-induced pressure wave mechanism. At higher cavitation numbers, the sheet cavity is relatively short and the cavity detachment is a consequence of a re-entrant jet pinching off the cavity from its leading edge. At lower cavitation numbers, the re-entrant jet plays a smaller role in the cavitation instabilities and the primary reason for periodic cloud shedding is the condensation shock mechanism where a void fraction discontinuity propagates upstream until collapsing the entire cavity. If the amount of shed vapour cloud reaches a certain extent, the collapse will emit a pressure wave strong enough to disturb the growing cavity, and subsequently make it detached from the wall. This is the third mechanism observed in the experiments. We point out the inappropriate classification of combining condensation shock and collapse-induced pressure wave mechanisms in the literature, since we identify pronounced differences between them: (i) the pressure increase across the condensation front is very weak (a few kPa) while the amplitude of collapse-induced pressure wave can be hundreds of kPa, (ii) the travelling velocity of the collapse-induced pressure wave within the cavity is much faster than the condensation shock, and (iii) the collapse-induced pressure wave does not result in an obvious discontinuity in void fraction when it propagates through the cavity, in contrary to the condensation shock.